Chest Pain Risk Scores Can Reduce Emergent Cardiac Imaging Test Needs With Low Major Adverse Cardiac Events Occurrence in an Emergency Department Observation Unit. Issue 4 (December 2016) - Wang, Hao; Watson, Katherine; Robinson, Richard D.; Domanski, Kristina H.; Umejiego, Johnbosco; Hamblin, Layton; Overstreet, Sterling E.; Akin, Amanda M.; Hoang, Steven; Shrivastav, Meena; Collyer, Michael; Krech, Ryan N.; et al.
Abstract : Objective: To compare and evaluate the performance of the HEART, Global Registry of Acute Coronary Events (GRACE), and Thrombolysis in Myocardial Infarction (TIMI) scores to predict major adverse cardiac event (MACE) rates after index placement in an emergency department observation unit (EDOU) and to determine the need for observation unit initiation of emergent cardiac imaging tests, that is, noninvasive cardiac stress tests and invasive coronary angiography. Methods: A prospective observational single center study was conducted from January 2014 through June 2015. EDOU chest pain patients were included. HEART, GRACE, and TIMI scores were categorized as low (HEART ⩽ 3, GRACE ⩽ 108, and TIMI ⩽1) versus elevated based on thresholds suggested in prior studies. Patients were followed for 6 months postdischarge. The results of emergent cardiac imaging tests, EDOU length of stay (LOS), and MACE occurrences were compared. Student t test was used to compare groups with continuous data, and χ 2 testing was used for categorical data analysis. Results: Of 986 patients, emergent cardiac imaging tests were performed on 62%. A majority of patients were scored as low risk by all tools (85% by HEART, 81% by GRACE, and 80% by TIMI, P < 0.05). The low-risk patients had few abnormal cardiac imaging test results as compared with patients scored as intermediate to high risk (1% vs. 11% in HEART, 1% vs. 9% in TIMI, and 2% vs. 4% in GRACE, P < 0.05). The average LOS was 33 hours for patients with emergent cardiac imaging tests performed and 25 hours for patients without ( P < 0.05). MACE occurrence rate demonstrated no significant difference regardless of whether tests were performed emergently (0.31% vs. 0.97% in HEART, 0.27% vs. 0.95% in TIMI, and 0% vs. 0.81% in GRACE, P > 0.05). Conclusions: Chest pain risk stratification via clinical decision tool scores can minimize the need for emergent cardiac imaging tests with less than 1% MACE occurrence, especially when the HEART score is used.